VQ-VAE-2를 활용한 향상된 동적 영상 생성 인공지능 - 이현준(Hyun-Jun Lee); 김지우(Ji-Woo Kim); 채상미(Sang-Mi Chae) (한국정보통신학회논문지, 2024)
본 연구는 인공지능(AI)을 활용한 콘텐츠 생산을 목표로 하고 있으며, 특히 영상 생성 분야의 급격한 발전에 주목하고 있다. 최근 영상 생성 모델에 대한 수요가 지속적으로 증가함에 따라, 본 연구에서는 VQ-VAE-2 프레임워크를 활용한 새로운 영상 생성 모델을 제안한다. 이 모델은 정지된 이미지를 동적인 영상 콘텐츠로 효과적으로 변환하도록 설계되었으며, AI 기반 영상 합성 분야에서 상당한 진전을 이룰 수 있는 가능성을 제시한다. TGIF 데이터셋을 사용하여 본 연구에서 제안하는 VQ-VAE-2 모델의 변형을 훈련한 결과, 단일 사진으로부터 고품질의 영상을 생성할 수 있는 모델을 성공적으로 개발하였다. 이 성과는 AI를 활용한 영상 제작의 가능성을 입증할 뿐만 아니라 창의적인 콘텐츠 생성에 대한 새로운 가능성을 열어준다. 더 나아가, VQ-VAE-2 모델의 훈련 과정에서 생성된 픽셀의 분포를 분석하여 자연 영상의 구조를 심도 있게 연구할 계획이다. 이러한 분석을 통해 이미지 합성의 기본 메커니즘에 대한 더 깊은 통찰을 제공하고, 혁신적인 응용을 위한 AI 활용에 대한 이해를 높이고자 한다. This study aims to produce content using AI, specifically focusing on the emerging field of video generation. In response to the rising demand for advanced video generation models, we propose a novel video generation approach utilizing the VQ-VAE-2 framework. This model is designed to efficiently transform still images into dynamic video content, offering significant advancements in the field of AI-driven video synthesis. By training a variation of the VQ-VAE-2 model with the TGIF dataset, we have successfully developed a model capable of generating videos from a single photo. This achievement not only demonstrates the potential of AI in video production but also opens up new possibilities for creative content generation. Furthermore, we plan to analyze the structure of natural images by examining the distribution of pixels generated during the training process of the VQ-VAE-2 model. This analysis will provide deeper insights into the underlying mechanisms of image synthesis, enhancing our understanding of how AI can be harnessed for innovative applications. KCI Citation Count: 0